Psychological therapies for children and adolescents exposed to trauma - Gillies, Donna (Cochrane Database Syst Rev, 2016)
BACKGROUND: Children and adolescents who have experienced trauma are at high risk of developing post‐traumatic stress disorder (PTSD) and other negative emotional, behavioural and mental health outcomes, all of which are associated with high personal and health costs. A wide range of psychological treatments are used to prevent negative outcomes associated with trauma in children and adolescents. OBJECTIVES: To assess the effects of psychological therapies in preventing PTSD and associated negative emotional, behavioural and mental health outcomes in children and adolescents who have undergone a traumatic event. SEARCH METHODS: We searched the Cochrane Common Mental Disorders Group's Specialised Register to 29 May 2015. This register contains reports of relevant randomised controlled trials from The Cochrane Library (all years), EMBASE (1974 to date), MEDLINE (1950 to date) and PsycINFO (1967 to date). We also checked reference lists of relevant studies and reviews. We did not restrict the searches by date, language or publication status. SELECTION CRITERIA: All randomised controlled trials of psychological therapies compared with a control such as treatment as usual, waiting list or no treatment, pharmacological therapy or other treatments in children or adolescents who had undergone a traumatic event. DATA COLLECTION AND ANALYSIS: Two members of the review group independently extracted data. We calculated odds ratios for binary outcomes and standardised mean differences for continuous outcomes using a random‐effects model. We analysed data as short‐term (up to and including one month after therapy), medium‐term (one month to one year after therapy) and long‐term (one year or longer). MAIN RESULTS: Investigators included 6201 participants in the 51 included trials. Twenty studies included only children, two included only preschool children and ten only adolescents; all others included both children and adolescents. Participants were exposed to sexual abuse in 12 trials, to war or community violence in ten, to physical trauma and natural disaster in six each and to interpersonal violence in three; participants had suffered a life‐threatening illness and had been physically abused or maltreated in one trial each. Participants in remaining trials were exposed to a range of traumas. Most trials compared a psychological therapy with a control such as treatment as usual, wait list or no treatment. Seventeen trials used cognitive‐behavioural therapy (CBT); four used family therapy; three required debriefing; two trials each used eye movement desensitisation and reprocessing (EMDR), narrative therapy, psychoeducation and supportive therapy; and one trial each provided exposure and CBT plus narrative therapy. Eight trials compared CBT with supportive therapy, two compared CBT with EMDR and one trial each compared CBT with psychodynamic therapy, exposure plus supportive therapy with supportive therapy alone and narrative therapy plus CBT versus CBT alone. Four trials compared individual delivery of psychological therapy to a group model of the same therapy, and one compared CBT for children versus CBT for both mothers and children. The likelihood of being diagnosed with PTSD in children and adolescents who received a psychological therapy was significantly reduced compared to those who received no treatment, treatment as usual or were on a waiting list for up to a month following treatment (odds ratio (OR) 0.51, 95% confidence interval (CI) 0.34 to 0.77; number needed to treat for an additional beneficial outcome (NNTB) 6.25, 95% CI 3.70 to 16.67; five studies; 874 participants). However the overall quality of evidence for the diagnosis of PTSD was rated as very low. PTSD symptoms were also significantly reduced for a month after therapy (standardised mean difference (SMD) ‐0.42, 95% CI ‐0.61 to ‐0.24; 15 studies; 2051 participants) and the quality of evidence was rated as low. These effects of psychological therapies were not apparent over the longer term. CBT was found to be no more or less effective than EMDR and supportive therapy in reducing diagnosis of PTSD in the short term (OR 0.74, 95% CI 0.29 to 1.91; 2 studies; 160 participants), however this was considered very low quality evidence. For reduction of PTSD symptoms in the short term, there was a small effect favouring CBT over EMDR, play therapy and supportive therapies (SMD ‐0.24, 95% CI ‐0.42 to ‐0.05; 7 studies; 466 participants). The quality of evidence for this outcome was rated as moderate. We did not identify any studies that compared pharmacological therapies with psychological therapies. AUTHORS' CONCLUSIONS: The meta‐analyses in this review provide some evidence for the effectiveness of psychological therapies in prevention of PTSD and reduction of symptoms in children and adolescents exposed to trauma for up to a month. However, our confidence in these findings is limited by the quality of the included studies and by substantial heterogeneity between studies. Much more evidence is needed to demonstrate the relative effectiveness of different psychological therapies for children exposed to trauma, particularly over the longer term. High‐quality studies should be conducted to compare these therapies.